ANALISIS SUBSISTEM AGRIBISNIS PADA USAHA SAYURAN HIDROPONIK BERBASIS NUTRIENT FILM TECHNIQUE (NFT) DI KOTA MEDAN STUDI KASUS PADA UMKM UDA SARAH - Hendra Saputra; Saniah Lidiya Hawani; Cris Diana Sidabutar; Heva Gracia Manurung; Joanna Brigitta; Aurel Ramadhanti Surya (Fakultas Pertanian, Program Studi Agroteknologi, 2026)
The development of urban agriculture through hydroponic technology is one solution toaddress land limitations and the increasing public demand for fresh and hygienic vegetables.This study aims to analyze the implementation of agribusiness subsystems in a hydroponicvegetable business based on Nutrient Film Technique (NFT) in Medan City with a case studyof the MSME